Transparent model concrete with tunable rheology for investigating flow and particle-migration during transport in pipes. (August 2020) - Auernhammer, Günter K.; Fataei, Shirin; Haustein, Martin A.; Patel, Himanshu P.; Schwarze, Rüdiger; Secrieru, Egor; Mechtcherine, Viktor
Abstract: The article describes the adaption and properties of a model concrete for detailed flow studies. To adapt the yield stress and plastic viscosity of the model concrete to the corresponding rheological properties of real concrete, the model concrete is made of a mixture of glass beads and a non-Newtonian fluid. The refractive index of the non-Newtonian fluid is adjusted to the refractive index of the glass beads by the addition of a further constituent. The rheological properties of the model concrete are characterised by measurements in concrete rheometers. Finally, the first exemplary results from experiments with the model concrete are presented, which give incipient impressions of the complex internal dynamics in flowing concrete. Graphical abstract: Unlabelled Image Highlights: Highly transparent material developed is suitable for modeling concrete. Refractive indexes of the model fluid and glass particles could be well matched. Model "concrete" exhibits rheological behaviour similar to that of real concrete. Particle size distribution, solid content, and rheology of model concrete can be varied. Model concrete is suitable for studying particle migration during concrete pumping.